Cobalt compounded Prussian blue aqueous sodium ion battery positive electrode material and preparation method thereof

Through the cobalt compounding and vacuum drying process in Prussian blue material, the problems of high moisture content and low specific capacity and rate performance of Prussian blue material are solved, and the specific capacity and rate performance are significantly improved. It is suitable for aqueous sodium ion batteries Practical application.

CN119252913APending Publication Date: 2025-01-03CHONGQING INST OF NEW ENE STOR MATER & EQUIP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411384655.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing Prussian blue materials have high moisture content and low specific capacity and rate performance in aqueous sodium ion batteries, making it difficult to meet the actual application needs.

Method used

Cobalt composite Prussian blue material is used to prepare CoMnHCF material by partially replacing manganese in MnHCF material, the content of the composite cobalt source is controlled, the moisture content of the material is reduced, and the specific capacity and rate performance of the material are improved through vacuum drying and grinding processes. .

Benefits of technology

The specific capacity and rate performance of the material have been significantly improved. The specific capacity of the CoMnHCF-50 material reaches 115.8mAh/g at a current density of 300mA/g, and the preparation process is efficient and safe, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252913A_ABST
    Figure CN119252913A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aqueous sodium-ion batteries, and discloses a cobalt compounded Prussian blue aqueous sodium-ion battery positive electrode material, which comprises an electrode active material, a conductive agent and a binder according to a mass ratio of 7: 2: 1, and the electrode active material is a CoMnHCF Prussian blue material. The preparation method comprises the following steps: weighing and mixing the CoMnHCF Prussian blue material, the conductive agent and the adhesive according to the mass ratio of 7: 2: 1, fully grinding, adding a proper amount of N-methyl pyrrolidone as a solvent, uniformly stirring to obtain uniform slurry, smearing the slurry on carbon cloth, and drying in a vacuum drying oven at 40-120 DEG C for 10-24 hours to obtain the CoMnHCF Prussian blue conductive carbon cloth. The cobalt compounded Prussian blue aqueous sodium ion battery positive electrode material is obtained. According to the technical scheme, the water content of the Prussian blue material can be reduced, and the specific capacity and the rate capability of the Prussian blue material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aqueous sodium ion batteries, and in particular to a cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of global industry and people's higher expectations for a better life, the existing fossil energy can no longer meet the market demand. At the same time, the serious environmental pollution caused by the combustion of fossil energy has prompted people to actively seek ways to replace fossil energy with clean renewable energy. However, clean renewable energy is constrained by factors such as geographical conditions, climate change and time dimension, and has the shortcomings of intermittency and randomness, so the development of energy storage technology is particularly critical. Among secondary batteries, lithium-ion batteries have been successfully applied in various portable electronic devices and electric vehicles due to their high energy density, long cycle life and excellent rate performance. However, with the continuous expansion of energy storage scale, limited lithium resources, safety hazards such as flammability and explosion, and high prices make it difficult to meet energy storage needs. In comparison, sodium-ion batteries have become the most promising partial substitute for lithium-ion batteries due to their abundant resources, wide distribution and similar physical and chemical properties to lithium. Among them, aqueous sodium-ion batteries have attracted much attention for their advantages such as high energy density, low cost, safety and environmental protection. Prussian blue materials have become widely used positive electrode materials due to their open framework structure, efficient and simple synthesis method and low cost. However, this material suffers from high water content and low specific capacity and rate performance, which greatly affects its practical application.

[0003] In the prior art, there are two main ways to reduce the moisture content of Prussian blue materials. One is heating, which evaporates the water by heating, but the control of temperature is a difficult point. When the temperature is too low, the water is difficult to remove effectively, and when the temperature is too high, the material structure will be destroyed. The other is ball milling, which can obtain highly crystalline materials, but its particle size and morphology are difficult to control accurately, which in turn affects the specific capacity and rate performance. Therefore, the synthesis of Prussian blue cathode materials suitable for aqueous sodium-ion batteries with low water content, high specific capacity and rate performance is still a technical problem that needs to be overcome. Summary of the invention

[0004] The present invention aims to provide a cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode material and a preparation method thereof, so as to reduce the water content of the material and improve its specific capacity and rate performance.

[0005] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode material, comprising an electrode active material, a conductive agent and a binder, the mass ratio of which is 7:2:1 respectively, and the electrode active material is CoMnHCF Prussian blue material.

[0006] Preferably, the method for preparing CoMHCF Prussian blue material comprises the following steps:

[0007] S1: Weigh a certain amount of manganese metal salt and cobalt metal salt respectively, and dissolve them in 20-200 mL of deionized water to form solution A, wherein the molar ratio of manganese metal salt to cobalt metal salt is (0.1-9):1;

[0008] S2: Weigh a certain amount of transition metal salt b and sodium salt respectively, dissolve them in 20-200 mL of deionized water to form solution B, wherein the molar ratio of transition metal salt b to sodium salt is 0.01-0.1;

[0009] S3: Slowly add solution A in S1 to solution B in S2, and keep stirring. After all solution A is added to solution B, continue stirring for 10-60 minutes, and then age for 1-24 hours;

[0010] S4: After the aging treatment, the CoMnHCF Prussian blue material is obtained by centrifugal separation, washing, vacuum drying and grinding.

[0011] Preferably, the concentration of the mixed solution of manganese metal salt and cobalt metal salt in S1 is 0.01-2 mol / L.

[0012] Preferably, the concentration of sodium salt in S2 is 0.001-3 mol / L.

[0013] Preferably, the concentration of transition metal salt b in S2 is 0.01-1 mol / L.

[0014] Preferably, the manganese metal salt in S1 is any one or a combination of MnCl2, Mn(NO3)2, MnSO4, and Mn(CH3COO)2.

[0015] Preferably, the cobalt metal salt in S1 is any one or a combination of CoSO4, Co(NO3)2, Co(CH3COO)2, and CoCl2.

[0016] Preferably, the transition metal salt b in S2 is any one of Na4Mn(CN)6, Na4Fe(CN)6, Na4Co(CN)6, Na4Ni(CN)6, Na4Cu(CN)6, and Na4Zn(CN)6.

[0017] Preferably, the vacuum drying temperature in S4 is 40-120° C., and the vacuum drying time is 10-24 h.

[0018] The present application also provides another technical solution, and the preparation method of the cobalt-compounded Prussian blue aqueous sodium-ion battery positive electrode material is as follows: CoMnHCF Prussian blue material, conductive agent and adhesive are weighed and mixed in a mass ratio of 7:2:1, and after sufficient grinding, an appropriate amount of N-methylpyrrolidone is added as a solvent, and after stirring evenly, a uniform slurry is obtained, and the slurry is applied on a carbon cloth, and placed in a vacuum drying oven at 40-120°C, and dried for 10-24 hours to obtain a cobalt-compounded Prussian blue aqueous sodium-ion battery positive electrode material.

[0019] Compared with the prior art, the beneficial technical effects of this technical solution are:

[0020] (1) The cobalt-compounded Prussian blue aqueous sodium-ion battery positive electrode material provided by the present technical solution is prepared by compounding cobalt in the MnHCF Prussian blue material to partially replace manganese, and controlling the content of the compounded cobalt source to obtain the CoMnHCF Prussian blue material, wherein the sodium content of CoMnHCF-50 is rich, and the phase structure is transformed into a sodium-rich monoclinic phase, and the specific capacity is significantly improved, reaching 115.8 mAh / g at a current density of 300 mA / g.

[0021] (2) The cobalt-compounded Prussian blue aqueous sodium-ion battery positive electrode material provided by this technical solution is a sodium-rich material with a reduced number of vacancies, which helps to reduce the water content, thereby providing Na + Providing more storage sites and larger ion channels, the aqueous sodium ion battery prepared using such materials as the positive electrode active material has better specific capacity and rate performance.

[0022] (3) The preparation method of the cobalt-compounded Prussian blue aqueous sodium-ion battery positive electrode material provided by the technical solution is efficient, safe and simple. The raw materials used are simple and easy to obtain, the production cost is low, the process is simple, and it is suitable for actual large-scale production fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD detection diagrams of CoMnHCF-50, CoMnHCF-30, CoMnHCF-70, MnHCF, and CoHCF prepared in Examples 1-3 and Comparative Examples 1-2 of the present invention;

[0024] Figure 2 The charge and discharge curves of the cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 of the present invention;

[0025] Figure 3 Thermogravimetric analysis (TGA) diagrams of CoMnHCF-50 and MnHCF prepared in Example 1 and Comparative Example 1 of the present invention;

[0026] Figure 4It is a rate performance test diagram of CoMnHCF-50 and MnHCF prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0027] The following is further described in detail through specific implementation methods:

[0028] Example 1

[0029] The cobalt-compounded Prussian blue aqueous sodium-ion battery positive electrode material includes an electrode active material, a conductive agent and a binder, and the mass ratio thereof is 7:2:1 respectively. The electrode active material is CoMnHCF Prussian blue material, the conductive agent is carbon black, and the binder is polyvinylidene fluoride.

[0030] The preparation method of CoMnHCF Prussian blue material comprises the following steps:

[0031] S1: Weigh a certain amount of manganese metal salt and cobalt metal salt respectively, dissolve them in 20-200mL deionized water to form solution A, wherein the molar ratio of manganese metal salt to cobalt metal salt is: (0.1-9): 1, the concentration of the mixed solution of manganese metal salt and cobalt metal salt is 0.01-2mol / L, the manganese metal salt is any one or a combination of MnCl2, Mn(NO3)2, MnSO4, Mn(CH3COO)2, and the cobalt metal salt is any one or a combination of CoSO4, Co(NO3)2, Co(CH3COO)2, and CoCl2; in this embodiment, weigh 3.2mmoL manganese chloride tetrahydrate and 3.2mmoL cobalt chloride hexahydrate, dissolve them in 50mL deionized water, and stir them thoroughly to form solution A, and the concentration of the mixed solution of manganese chloride tetrahydrate and cobalt chloride hexahydrate in S1 is 0.128mol / L;

[0032] S2: Weigh a certain amount of transition metal salt b and sodium salt respectively, dissolve them in 20-200mL deionized water to form solution B, wherein the molar ratio of transition metal salt b to sodium salt is: 0.01-0.1, the concentration of sodium salt is 0.001-3mol / L, the concentration of transition metal salt b is 0.01-1mol / L, transition metal salt b is any one of Na4Mn(CN)6, Na4Fe(CN)6, Na4Co(CN)6, Na4Ni(CN)6, Na4Cu(CN)6, Na4Zn(CN)6, and sodium salt is any one of NaCl, Na2SO4, NaNO3, CH3COONa or a combination of several thereof; in this embodiment, 14g sodium chloride and 1.42g sodium ferrocyanide are dissolved in 100mL deionized water and stirred thoroughly to form solution B, the concentration of sodium chloride is 2.4mol / L, and the concentration of sodium ferrocyanide is 0.0467mol / L;

[0033] S3: slowly drop solution A in S1 into solution B in S2, and stir continuously with a magnetic stirrer at 25°C. After all solution A is added dropwise to solution B, continue stirring for 10-60 minutes, and then age the obtained suspension for 1-24 hours. In this embodiment, the stirring time is 15 minutes and the aging time is 2 hours.

[0034] S4: After the aging treatment, the product is separated by centrifugation and washed three times with a washing solvent. The obtained product is placed in a vacuum oven and dried at 40-120°C for 10-24h. After sufficient grinding, a CoMnHCF Prussian blue material is obtained, which is named CoMnHCF-50 material; wherein the washing solvent is any one or a combination of deionized water, ethanol, and acetone. In this embodiment, deionized water is selected as the washing solvent, the drying temperature is 60°C, and the drying time is 18h.

[0035] The preparation method of the cobalt-compounded Prussian blue aqueous sodium-ion battery positive electrode material is as follows: CoMnHCF Prussian blue material, a conductive agent and an adhesive are weighed and mixed in a mass ratio of 7:2:1, and after sufficient grinding, an appropriate amount of N-methylpyrrolidone is added as a solvent, and after stirring evenly, a uniform slurry is obtained, and the slurry is evenly and evenly applied on the treated carbon cloth, and placed in a 40-120° C. vacuum drying oven, and dried for 10-24 hours to obtain a cobalt-compounded Prussian blue aqueous sodium-ion battery positive electrode material. In this embodiment, the conductive agent is carbon black, the adhesive is polyvinylidene fluoride, the amount of the conductive agent is 5.7 mg, the amount of the adhesive is 2.9 mg, the amount of the CoMnHCF Prussian blue material is 20 mg, the amount of N-methylpyrrolidone is 400 uL, the drying temperature is 60° C., and the drying time is 12 hours.

[0036] The test conditions of electrochemical performance are: at 25° C., the constant current charge and discharge test of the battery adopts LANHECT2001A battery test system, the test voltage window is set to 0-1.2V, and the current density is 300-2000mA / g. The test conditions of Examples 1-3 and Comparative Examples 1-2 are the same.

[0037] Example 2

[0038] Different from Example 1, in the preparation method of the CoMnHCF Prussian blue material, in S1, 4.48 mmol manganese chloride tetrahydrate and 1.92 mmol cobalt chloride hexahydrate were dissolved in 50 mL deionized water and stirred thoroughly to form solution A, and the remaining steps were the same, and the CoMnHCF Prussian blue material was obtained in S4, named CoMnHCF-30.

[0039] Example 3

[0040] Different from Example 1, in the preparation method of the CoMnHCF Prussian blue material, in S1, 1.92 mmol manganese chloride tetrahydrate and 4.48 mmol cobalt chloride hexahydrate are dissolved in 50 mL deionized water and stirred thoroughly to form solution A, and the remaining steps are the same, and the CoMnHCF Prussian blue material is obtained in S4, which is named CoMnHCF-70.

[0041] Comparative Example 1

[0042] Different from Example 1, in the preparation method of CoMnHCF Prussian blue material, in S1, no cobalt metal salt is used, 6.4 mmol of manganese chloride tetrahydrate is dissolved in 50 mL of deionized water and stirred thoroughly to form solution A, and the remaining steps are the same, and a Prussian blue material is obtained in S4, which is named MnHCF.

[0043] Comparative Example 2

[0044] Different from Example 1, in the preparation method of CoMnHCF Prussian blue material, in S1, no manganese metal salt is used, 6.4 mmol of cobalt chloride hexahydrate is dissolved in 50 mL of deionized water and stirred thoroughly to form solution A, and the remaining steps are the same. In S4, a Prussian blue material is obtained and named CoHCF.

[0045] The dosage of each component in Examples 1-3 and Comparative Examples 1-2 is shown in Table 1:

[0046] Table 1

[0047] Dosage Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Amount of substance of manganese chloride tetrahydrate (mmoL) 3.2 4.48 1.92 6.4 0 Amount of substance of cobalt chloride hexahydrate (mmoL) 3.2 1.92 4.48 0 6.4 Concentration of solution A (mol / L) 0.128 0.128 0.128 0.128 0.128 Mass of sodium chloride (g) 14 14 14 14 14 Mass of sodium ferrocyanide (g) 1.42 1.42 1.42 1.42 1.42 Sodium chloride concentration (mol / L) 2.4 2.4 2.4 2.4 2.4 Concentration of sodium ferrocyanide (mol / L) 0.0467 0.0467 0.0467 0.0467 0.0467

[0048] XRD detection was performed on CoMnHCF-50, CoMnHCF-30, CoMnHCF-70, MnHCF, and CoHCF materials prepared in Examples 1-3 and Comparative Examples 1-2. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the diffraction peak of the CoMnHCF material after compounding with cobalt shifts to a larger angle than that of MnHCF, indicating that the interplanar spacing is reduced, which is beneficial to the rapid redox reaction of the transition metal in the material, thereby improving the rate performance; in addition, the crystal structure of CoMnHCF-30, CoMnHCF-50 and CoMnHCF-70 materials is transformed from the cubic phase of MnHCF to the sodium-rich monoclinic phase.

[0049] The cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to charge and discharge tests, and the results are as follows: Figure 2 As shown in Table 2, Figure 2 Table 2 and Table 3 show the specific capacities of Examples 1-3 and Comparative Examples 1-2 at a current density of 300 mA / g. Figure 2 It can be seen that before the CoMnHCF-50 material, as the amount of cobalt metal salt increased, its first-cycle specific capacity also increased. After the CoMnHCF-50 material, as the amount of cobalt metal salt increased, its first-cycle specific capacity decreased. Therefore, the first-cycle specific capacity of the CoMnHCF-50 material is optimal, and the specific capacity can reach 115.8 mAh / g at a current density of 300 mA / g.

[0050] Table 2

[0051] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Specific capacity (mAh / g) 115.8 100.5 108.2 35.4 107.4

[0052] The CoMnHCF-50 and MnHCF prepared in Example 1 and Comparative Example 1 were tested by inductively coupled plasma optical emission spectrometry (ICP-OES), and the test results are shown in Table 3. From the data in Table 3, it can be calculated that the molecular formulas of MnHCF and CoMnHCF-50 are Na 1.15 Mn[Fe(CN)6] 0.73 、Na 1.79 Co 0.74 Mn 0.26 [Fe(CN)6] 0.82 From the molecular formula, it can be seen that the Na content in CoMnHCF-50 is significantly increased, which is a sodium-rich material, which helps to improve the specific capacity, reduce the number of vacancies, and help reduce the water content.

[0053] Table 3

[0054] Mass percentage (wt%) Na Mn Co Fe Comparative Example 1 (MnHCF) 9.701 20.222 15.044 Example 1 (CoMnHCF-50) 11.122 3.923 11.727 12.356

[0055] The CoMnHCF-50 and MnHCF prepared in Example 1 and Comparative Example 1 were subjected to thermogravimetric analysis (TGA). The results are as follows: Figure 3 As shown, from Figure 3 It can be seen that the water content (adsorbed water and lattice water) of CoMnHCF-50 is significantly reduced, which can be + Providing more storage sites and larger ion channels helps to improve specific capacity and rate performance.

[0056] The CoMnHCF-50 and MnHCF prepared in Example 1 and Comparative Example 1 were tested for rate performance, and the results are as follows: Figure 4 As shown, from Figure 4 It can be seen that MnHCF is rapidly destroyed in the first cycle, while CoMnHCF-50 has a higher rate performance of 73.2% at 2000 mA / g.

[0057] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. Cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode material, characterized by: The invention comprises an electrode active material, a conductive agent and a binder, wherein the mass ratios thereof are 7:2:1 respectively, and the electrode active material is a CoMnHCF Prussian blue material.

2. The cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode material according to claim 1, characterized in that: The preparation method of CoMnHCF Prussian blue material comprises the following steps: S1: Weigh a certain amount of manganese metal salt and cobalt metal salt respectively, and dissolve them in 20-200 mL of deionized water to form solution A, wherein the molar ratio of manganese metal salt to cobalt metal salt is (0.1-9):1; S2: Weigh a certain amount of transition metal salt b and sodium salt respectively, dissolve them in 20-200 mL of deionized water to form solution B, wherein the molar ratio of transition metal salt b to sodium salt is 0.01-0.1; S3: Slowly add solution A in S1 to solution B in S2, and keep stirring. After all solution A is added to solution B, continue stirring for 10-60 minutes, and then age for 1-24 hours; S4: After the aging treatment, the CoMnHCF Prussian blue material is obtained by centrifugal separation, washing, vacuum drying and grinding.

3. The cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode material according to claim 2, characterized in that: The concentration of the mixed solution of manganese metal salt and cobalt metal salt in S1 is 0.01-2 mol / L.

4. The cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode material according to claim 3, characterized in that: The concentration of sodium salt in S2 is 0.001-3 mol / L.

5. The cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode material according to claim 4, characterized in that: The concentration of transition metal salt b in S2 is 0.01-1 mol / L.

6. The cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode material according to claim 5, characterized in that: The manganese metal salt in S1 is any one of MnCl2, Mn(NO3)2, MnSO4, and Mn(CH3COO)2, or a combination of several of them.

7. The cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode material according to claim 6, characterized in that: The cobalt metal salt in S1 is any one or a combination of CoSO4, Co(NO3)2, Co(CH3COO)2, and CoCl2.

8. The cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode material according to claim 7, characterized in that: The transition metal salt b in S2 is any one of Na4Mn(CN)6, Na4Fe(CN)6, Na4Co(CN)6, Na4Ni(CN)6, Na4Cu(CN)6, and Na4Zn(CN)6.

9. The cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode material according to claim 8, characterized in that: The vacuum drying temperature in S4 is 40-120°C, and the vacuum drying time is 10-24h.

10. The method for preparing the cobalt-compounded Prussian blue aqueous sodium ion battery positive electrode material according to claim 9, characterized in that: The CoMnHCF Prussian blue material, the conductive agent and the adhesive are weighed and mixed in a mass ratio of 7:2:

1. After being fully ground, an appropriate amount of N-methylpyrrolidone is added as a solvent. After being stirred evenly, a uniform slurry is obtained. The slurry is applied on a carbon cloth and placed in a vacuum drying oven at 40-120°C for drying for 10-24 hours to obtain a cobalt-compounded Prussian blue aqueous sodium-ion battery positive electrode material.

Citation Information

Patent Citations

  • Sodium-ion battery Prussian blue positive electrode material and preparation method and application thereof

    CN113526527A